ANALISIS PRILAKU KONSUMTIF MAHASISWA UNIVERSITAS ISLAM NEGERI SUMATERA UTARA DALAM PERSPEKTIF EKONOMI ISLAM - Abdul Aziz Hakim; Elya Rosa Maharani Sembiring; Dini Lestari; Muhammad Ikhsan Harahap (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
Consumptive behavior is the urge to follow trends and fashions that are developing, as well as the desire to be noticed by others. The purpose of this study seeks to measure the extent of consumerism among students at the State Islamic University of North Sumatra. The research method used is descriptive qualitative research, which seeks to describe, describe the data with words/explanation of a problem, and describe the data. People of various ages and status became research informants. The results of this study explain that consumptive behavior is not very good in everyday life. And in Islam consumptive behavior is strictly not allowed and Islam strictly prohibits excessive behavior. According to research, globalization is one of the key variables affecting consumption. Consumptive excesses have a detrimental effect on a country's economy, which is not ideal from an Islamic point of view.